Hétérochronie et décolonisation - Seloua Luste Boulbina (Socio, 2024)
Decolonization is often seen as a solution whose theoretical simplicity runs up against practical difficulties. My aim here is to show, on the contrary, how decolonization is a complex idea whose realization in practice must take account of decisive factors such as space and time. On either side of the old imperial-colonial frontier, whose walls have not yet completely come down, decolonization has neither the same meaning nor the same scope, nor the same stakes.